(untitled) (Journal of Misan Researches, 2023)
The ancient Iraqi art (Sumerian art) and what celebrates many symbols and signs were effective in this art, such as the artist’s tendency in Iraqi art to contemplative thought with his religious faith and myths, which brought him to an atmosphere of symbolic abstraction that preceded other similar arts. And to show the effect on the knowledge of the old and its effect on the new, that is, the effect of the old on the new, or it is produced in a new way, and since the students of the Department of Art Education - College of Fine Arts / University of Baghdad who were affected by ancient Iraqi art, especially the symbols that appeared in the students’ products, hence the problem of the current research, where the research answers the following question: - Did artistic symbols appear in ancient Iraqi art among the products of art education students? What are its meanings? The current research aims to: 1- Revealing symbols in ancient Iraqi art (Sumerian art) and their implications. 2- Revealing symbols in ancient Iraqi art (Sumerian art) in the products of art education students. Since the current research aims to reveal the Sumerian symbols and their connotations in the products of the projects of the students of the Department of Art Education, so the researcher followed the descriptive approach - the method of content analysis, being the most appropriate scientific method to achieve the goal of the research, as the research community consists of the outputs of the graduation projects for the students of the Department of Art Education Which were completed in (2020/2021), numbering 54, with two jobs for each student, where the total becomes (108) artworks in the field of drawing, an intentional sample of graduation projects for students of the Department of Art Education - Morning Studies, which amounted to (5) artworks The Sumerian symbols and their connotations, which are the essence of the research goal represented by the symbols and their connotations in the ancient Iraqi art (Sumerian) and its reflections on the products of art education students. 1- The singular symbol: the human symbol appeared in a degree that it appears strongly in the forms (1, 3, 5) and to a degree that it does not appear in the forms (2, 4). 2- The complex symbol: the natural + natural symbol appeared to a degree that appears strongly in the models (1, 5) and to a degree that is lesser in the models (2, 3, 4).